2021
DOI: 10.1038/s41598-021-89594-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of auditory sensations in patients who underwent cataract phacoemulsification surgery in the first and second eye

Abstract: To compare subjective auditory sensations of patients during the first and second eye cataract surgeries. Consecutive patients who underwent phacoemulsification of the first eye (group I) and second eye (group II) completed questionnaires designed to evaluate their auditory sensations in the operating room including background music, sound of working equipment, staff conversations, and surgeon’s voice. This study included 124 patients in group I and 76 patients in group II. Patients most often heard nursing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The calm voice of the surgeon has a very positive effect on calming the patient during the operation, explaining that the operation is as planned, nothing wrong is happening, and the procedure will end soon. 13 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…The calm voice of the surgeon has a very positive effect on calming the patient during the operation, explaining that the operation is as planned, nothing wrong is happening, and the procedure will end soon. 13 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…One RCT from 2022 showed that in a group of patients that received no preoperative sedation, nonfasting prior to cataract surgery significantly decreases preoperative anxiety, surgical pain, and operative time, suggesting that the fasting requirement before surgery with pharmacological sedation may itself negatively affect outcomes [59 ▪ ]. Intraoperative interventions such as calming surgeon verbalization [31 ▪ ,60] and music, particularly with binaural beat audio, have also been shown to decrease patient anxiety [61,62]. As the office-based setting becomes more common for cataract surgery, and possibly for some other anterior segment surgeries, surgeons should consider a holistic approach to anxiolysis with options that can augment or preclude pharmacologic sedation.…”
Section: No Sedation and Non-pharmacologic Anxiolytic Techniquesmentioning
confidence: 99%